A quality improvement study: Optimizing pneumococcal vaccination rates in children with cochlear implants. Issue 32 (30th July 2022) - Tay, S.; Bowen, A.C.; Blyth, C.C.; Clifford, P.; Clack, R.; Ford, T.; Herbert, H.; Kuthubutheen, J.; Mascaro, F.; O'Mahoney, A.; Rodrigues, S.; Tran, T.; et al.
Highlights: Cochlear implant recipients are at higher risk of invasive pneumococcal disease. Most pediatric cochlear implants recipients were overdue pneumococcal vaccines. Generic and personalized electronic reminders improved pneumococcal vaccine uptake. A targeted nurse-led immunization clinic improved pneumococcal vaccination rates. Abstract: Children with cochlear implants are at increased risk of invasive pneumococcal disease, with national and international guidelines recommending additional pneumococcal vaccines for these children. This study aimed to examine the pneumococcal immunization status and rate of invasive pneumococcal disease in children with cochlear implants at a tertiary paediatric hospital over a 12-year period. Additionally, the impacts of vaccination reminders and a dedicated immunization clinic on pneumococcal vaccination rates were assessed. This quality improvement study included 200 children who had received a cochlear implant through the Children's Hearing Implant Program at a tertiary paediatric hospital servicing the state of Western Australia. The majority of children (88%) were not up to date with additionally recommended pneumococcal vaccinations. Over the 12-year study period, 2% of children developed invasive pneumococcal disease associated with cochlear implant infections. Generic and personalized electronic immunization reminders improved pneumococcal vaccine up-take in this paediatric cochlear implant setting from 12% (19/153) at baseline to 49% (75/153, p < 0.0001) post implementation. The value of a nurse-led dedicated immunization clinic was also demonstrated with all children (42/42, 100%) up to date with Prevenar13 and the majority (34/42, 81%) up to date with Pneumovax23 post initiation of this referral pathway. These data support the expansion of this model to other medically-at-risk paediatric groups that have been highlighted consistently to be under-vaccinated.